VASOCONSTRICTIVE EFFECT OF XINMAILONG IN RAT AORTA - Yang, Cui; Zhang, Lifang; Dai, Rong; Ji, Siping; Li, Fang; shao, Weizai; Que, Yuling; Hu, Ling; Lin, Qing (African Journal of Traditional, Complementary and Alternative Medicines, 2015)
Background: Cockroach has been utilized traditionally in China for the therapy of cardiovascular disorders, such as heart failure. The present study was aimed to assess the vasoconstrictive effect of Xinmailong Injection (XML), a bioactive composite from American cockroach. Methodology: The isometric tensions of rat aortic rings were measured after acutely treated with XML. Meanwhile, the systemic blood pressures (SBPs) were recorded and the levels of the endothelium-derived cytokines in blood samples were detected after rats were administered with XML for 3 days. Protein expression for the L-type Ca2+ channels (Cav1.2) was also determined in rat thoracic aorta. Results: XML induced vasoconstrictions in rat aortic rings with or without endothelium. In addition, the vasoconstrictions due to extracellular Ca2+ influx and intracellular Ca2+ release were also elevated by XML. After treatment with XML for 3 days, the levels of prostacyclin (PGI2) were markedly elevated whereas the levels of nitric oxide (NO) and endothelin-1 (ET-1) were not significantly changed in rats. Furthermore, expression of the Cav1.2 protein was significantly enhanced in aorta but the SBPs of rats were not influenced.Conclusion: XML plays an important role in regulating vascular tone. The increases of the extracellular Ca2+ influx and the intracellular Ca2+ release may contribute to the vasoconstriction induced by XML. Our findings pave the ways to better understand the therapeutic effects of XML on cardiovascular system.